The Motivational Influence of Milestone Times on 10-km Running Performance. (1st August 2016) - Cushman, M. Daniel; Babu, Ashwin; Marshall, Benjamin; Rho, Monica
Abstract : To date, little research has been conducted to evaluate the potentially motivating effect of completing a race at a specific "milestone" finishing time. As this is difficult to perform in a laboratory setting, we examined 10-km runners from a large cohort to see if they were more likely to complete a race before rather than after a set milestone time (40:00, 45:00, and 50:00). Frequency distributions for finishers of each sex were created in 30-second time groups, with ideal normal distributions modeled based on this data. The actual time group frequencies were compared to the "expected" values from the modeled normal distributions. We included time groups that contained at least 1, 000 finishers, thus were constrained to 36:00 – 52:00 for men and 43:30 to 52:00 for women. A total of 180, 731 men and 53, 047 women were included in the analysis. Men showed significant positive deviations (more finishers than expected) in the 39:30-40:00, 44:30-45:00, and 48:30-50:00 time groups (3 groups); they showed significant negative deviations only at 40:00-40:30 and 50:00-50:30. Women only showed significant positive time group deviations from 48:30-50:00 (1 group) with no significant negative deviations. In conclusion, despite the relatively arbitrary nature of milestones, they appear to exert a motivational influence on 10-km runners.